Ellagic acid reduces methotrexate-induced apoptosis and mitochondrial dysfunction via up-regulating Nrf2 expression and inhibiting the IĸBα/NFĸB in rats - Ebrahimi, Reihaneh (Daru, 2019)
BACKGROUND: The clinical application of methotrexate (MTX), an efficacious cytotoxic drug, is restricted due to its associated liver toxicity. Ellagic acid (EA), a natural polyphenol, possesses hepatoprotective, antioxidant and anti-inflammatory properties. OBJECTIVES: The present study seeks to address the hepatoprotective effects of Ellagic acid (EA) against MTX-mediated oxidative stress (OS) and widen our current knowledge of the underlying molecular mechanisms of MTX toxicity. METHODS: Wistar rats were orally given EA (5 mg/kg and 10 mg/kg) for 10 successive days and at the end of the third day they were administered a single dose of MTX (20 mg/kg i.p). RESULTS: After performing biochemical analysis, liver enzymes and malondialdehyde were significantly higher in the MTX group, indicating hepatic oxidative damage. MTX-induced OS was further confirmed with observation of events such as reactive oxygen species (ROS) overproduction, mitochondrial outer membrane potential decrease, mitochondrial swelling, cytochrome c release and caspase-3/9 increase, resulting in apoptosis. Furthermore, overexpression of pro-inflammatory factors such as nuclear factor kappa B (NF-ĸB) and interleukin 6 (IL-6) indicated the MTX-induced inflammation in MTX-treated group. Interestingly, EA was able to significantly prevent OS, mitochondrial dysfunction, apoptosis and inflammation induced by MTX. Also, EA-treated rats demonstrated significant upregulation of both nuclear factor erythroid 2-related factor 2 (Nrf2) and hemoxygenase-1 (HO-1), which were considerably downregulated in MTX-treated rats. CONCLUSIONS: EA protects rats against MTX-induced apoptosis and mitochondrial dysfunction via up-Regulating Nrf2 and HO-1 expression and inhibiting the NF-κB signaling pathway. Therefore, EA may protect patients against MTX-induced hepatotoxicity and encourage its clinical application. [Figure: see text]